Biliary metal stents for proximal esophageal or hypopharyngeal strictures - Bechtler, Matthias; Jakobs, Ralf (Surgical endoscopy and other interventional techniques, 2015)
Introduction Endoscopic dilation is the standard of care for stenoses of the cervical esophagus, but refractory strictures require some form of stenting. Most endoscopists avoid the placement of metal stents near the upper esophageal sphincter as they can cause major problems like severe cervical pain and globus sensation. We report our results with the use of biliary SEMS in the upper esophagus, which have a smaller diameter than regular esophageal stents and therefore exert less expansive force.Material and methods We retrospectively reviewed all patients in our center between July 2011 and June 2014 who received a biliary metal stent because of a refractory stricture in the cervical esophagus. We implanted biliary SEMS (Wallflex, Boston Scientific) with a diameter of 1 cm and length of 6-8 cm. Technical and clinical success, adverse events and duration of stenting were evaluated.ResultsTen patients were treated with biliary SEMS in the upper esophagus. Strictures were located between 10 and 19 cm from incisor teeth. Stent placement was successful in all (10/10) patients. One stent had to be extracted because of pain and globus sensation. Apart from that stent tolerability was good. All remaining patients (9/9) reported improvement of dysphagia with a decrease in mean dysphagia score from 3.2 to 1.78. Mean duration of stenting was 68 days.Discussion Because of a high clinical success rate and good tolerability, biliary metal stents are a reasonable alternative for difficult strictures in the cervical esophagus, especially in the palliative setting.